Análise térmica e energética do revestimento refratário de panelas de aço via modelos computacionais - Santos, Matheus Felipe (Universidade Federal de São Carlos, 2018)
The secondary metallurgy is an energy-intensive step in the steelmaking process that requires an accurate adjustment of the composition and temperature of the molten metal during the ladle refining. In this context, the steel ladle lining plays an important role on the energy consumption of the ladle processes, as the refractory thermal properties are strictly related to the ladle ability to keep constant the molten metal temperature. Aiming to improve the energy efficiency, reducing both costs and the environmental impacts, a transient numerical analysis of the ladle processes was developed using temperature dependent refractory properties. The present work proposes a holistic view of the ladle operational cycle to help the refractory design of such installations, according to their saving energy capability. The finite element modeling (FEM) was developed using a commercial software (Abaqus) to simulate the ladle cycle (pre-heating, holding and waiting steps). The temperatures predicted by the model were compared with in situ temperature data from a steel ladle to validate the model and the comparison showed good agreement between those temperatures. The results point out how the configurations with lining insulation reduces the energy consumption, keeping the molten steel temperatures higher, although it is mostly effective on reducing the shell temperatures. The safety lining could be replaced by more advanced materials with suitable properties or had its thickness reduced for expanding the working capacity and also saving energy. The refractories for the working layer application should have low or none carbon content and advanced materials for higher savings should be investigated. Computational models could indicate possible material designs and configuration solutions for the steel and refractory industries. In general, these solutions depend on each steel plant requirements, but some trends can be highlighted for improving the steel ladle energy efficiency, considering the refractory design for avoiding heat losses.
Thermal and energy analysis on steel ladle refractory lining via computational simulations
Keywords: Panela de aço; Refratário; Simulação; Perdas térmicas; Energia; Steel ladle; Refractory; Simulation; Energy; Heat losses; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS